Controle droop para regulador de tensão em sistemas ilhados com geração distribuida - Bastos, Elieser do Prado (2022)
A country with continental territorial extension such as Brazil has a vast network of power distribution and transmission networks, however, energy demands are not constantly met. A viable solution is the use of autonomous networks in an islanded mode, where hybrid systems meet the need for local energy demand. This dissertation proposes a study on Droop Control, in the context of parallelism with energy storage systems and voltage regulation on the AC bus. In this context, there are integrations of single-phase hybrid networks in islanded mode, which are interactions that include external current sources such as solar energy inverters and loads that will act by destabilizing the AC bus voltage. Not being connected to the National Interconnected System, the model needs components that prioritize, mainly, the stability of this voltage, because of this, a real case was surveyed for the collection of samples aiming at the verification of the variables of interest, for the designing a circuit in which the Droop Control interacts harmoniously in series with other controls. It is then proposed to simulate the connection of two battery banks, which use local variables such as voltage and current for their regulation, this information, in turn, is processed by the series controls, providing the necessary parameters to stabilize the voltage in the AC bus.